2013
DOI: 10.1179/1754762813y.0000000044
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant outcomes in patients with superior canal dehiscence

Abstract: Our data suggest that patients with asymptomatic superior canal dehiscence at the time of CI surgery have similar albeit decreased speech perception scores compared to non-SCD adult CI users. Subjective rate of dizziness or vertigo following CI surgery was similar in both asymptomatic SCD and non-SCD cohorts, with detailed analyses of a single symptomatic SCD patient revealing improved vestibular function and reduced SCD symptoms following CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In patients older than 18 years, 37 of 116 studies reported postoperative vertigo. A total of 16.8% (446 of 2,651) suffered from vertigo after cochlear implantation . Figure shows the mean age‐correlated occurrence of vertigo after cochlear implantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients older than 18 years, 37 of 116 studies reported postoperative vertigo. A total of 16.8% (446 of 2,651) suffered from vertigo after cochlear implantation . Figure shows the mean age‐correlated occurrence of vertigo after cochlear implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Patients of studies undergoing the RW approach do not have significantly increased vertigo after cochlear implantation, in contrast to studies including patients undergoing cochleostomy. Postoperative vertigo (new onset and perioperatively unchanged vertigo) occurred in 8.8% (532 of 6,120 patients) after cochleostomy and in 5.5% (48 of 868) after RW approach . Patients undergoing RW approach have a significantly lower risk of postoperative vertigo compared with cochleostomy (OR of 0.61; 95% CI 0.45–0.83; P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1720 Large dehiscences can be repaired by either occluding the SCD itself or by occluding both exposed ends of the canal. In this study, we created dehiscences of 0.5 to 3.5 mm in length that are typically repaired by occluding the SCD itself.…”
Section: Resultsmentioning
confidence: 99%
“…The association of superior semicircular canal dehiscence with other ear diseases [9,4,27] and other dehiscences produced in the bone labyrinth is currently being investigated.…”
Section: Introductionmentioning
confidence: 99%